Computer‐Aided Analysis of the Corrosion Inhibition by Carbon‐Based Thin‐Film Coating on Vascular Bare Metal Stent Models. Issue 8 (22nd June 2022) - Akdogan, Gulsen; Istanbullu, Omer Burak
Abstract: A simulation study of inhibiting the corrosion and corrosion‐based restenosis is presented by diamond‐like carbon (DLC) thin‐film coating on bare‐metallic intravascular stent models. The stents are designed and placed in a blood vessel model including a fatty‐plaque layer in the study. 316L‐stainless steel, CoCr‐alloy, and nitinol are assigned to the stent models considering stent manufacturing. Modeled stents are coated with a carbon‐based structure that mimics the DLC thin film. The electrochemical simulations are performed under the dynamic non‐Newtonian blood flow condition for a 1 year period. Electrolytic current densities, corrosion, and restenosis rates of the bare and coated stents are simulated using time‐dependent laminar flow and corrosion modules in multiphysics analysis software. Among the bare‐stent models, the highest corrosion rate is observed for 316L with 79 µm year −1 and the minimum corrosion rate is observed for nitinol with 9 µm year −1 . Restenosis rates increase up to 36 µm year −1 due to the charged‐particle adhesion on the bare stent surfaces. However, DLC‐thin‐film coating reduces corrosion and in‐stent restenosis (ISR) rates down to 0.94 and 0.2 µm year −1 respectively. It can be concluded that surface passivation by thin‐film DLC coating may be considered a promising candidate for novel stent designs having lower corrosion‐based issues and ISR risks. Abstract : The corrosion protection by diamond‐like carbon (DLC) thin‐film coating on 316L, CoCr alloy, and nitinol vascular stent models is simulated under dynamic blood‐flow conditions. 79 µm year −1 corrosion and 36 µm year −1 restenosis rates of 316L stents, 9.3 µm year −1 corrosion, and 4.6 µm year−1 restenosis rates of nitinol stents reduced to 0.94 and 0.2 µm year −1 by DLC coating.